2015
DOI: 10.1111/tbj.12495
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Human Burden of Breast Cancer: Advanced Radiation Therapy Yields Improved Treatment Outcomes

Abstract: Radiation therapy is an important modality in the treatment of patients with breast cancer. While its efficacy in the treatment of breast cancer was known shortly after the discovery of x-rays, significant advances in radiation delivery over the past 20 years have resulted in improved patient outcomes. With the development of improved systemic therapy, optimizing local control has become increasingly important and has been shown to improve survival. Better understanding of the magnitude of treatment benefit, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 113 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…It might be involved in that peculiar anatomy of the male mammary included less fat tissue, and the proposed ‘gas station’ effects of fat tissue on residual carcinoma cell will be cut 40 . Furthermore, we observed that the better prognosis was acquired when accepting radiation therapy and/or chemotherapy compared with those without adjuvant therapies, and consistent benefits were identified regardless of early or advanced BC 41 , 42 . Moreover, a recent study examined the effect of target-adjuvant drugs like mechanistic target of rapamycin (mTOR) inhibitors on subsets of MBC who was identified by transcriptomic investigation 43 , expectedly, and more practicable treatments will be utilized for MBC to improve prognosis.…”
Section: Discussionmentioning
confidence: 57%
“…It might be involved in that peculiar anatomy of the male mammary included less fat tissue, and the proposed ‘gas station’ effects of fat tissue on residual carcinoma cell will be cut 40 . Furthermore, we observed that the better prognosis was acquired when accepting radiation therapy and/or chemotherapy compared with those without adjuvant therapies, and consistent benefits were identified regardless of early or advanced BC 41 , 42 . Moreover, a recent study examined the effect of target-adjuvant drugs like mechanistic target of rapamycin (mTOR) inhibitors on subsets of MBC who was identified by transcriptomic investigation 43 , expectedly, and more practicable treatments will be utilized for MBC to improve prognosis.…”
Section: Discussionmentioning
confidence: 57%